Notes for a history of anthropology in Peru: the unpublished ethnography of Alejandro Vivanco and ethnological studies in the Chancay valley - Rivera Andía, Juan Javier (2001)
This article explores the paradigms that inspired anthropological research in Peru at the beginning of the second half of the 20th century. We will approach these years, crucial in anthropological reflection, through the work produced around a region of Lima (the communities of the Chancay valley). This work contains two contrasting cases: the works of Alejandro Vivanco, anthropologist and disciple of Arguedas, almost completely unpublished to date; and the books published under the direction of José Matos Mar, contemporary of Arguedas.